An Autoethnographic Vignette: The Case of Tax Relief and Sibling Caregivers In Malaysia - Devi, S. Susela; Nair, Siva Subramanian (Asian Journal of Business and Accounting, 2017)
Autoethnography is a research approach which uses self-reflection and writing to explore a particular phenomenon but it is seldom used in the business and accounting field. Nevertheless, the autoethnographic approach is not without its benefits and this paper thus advocates using the autoethnographic approach as a way of understanding the trials and tribulations of sibling caregivers of persons with disability. Through this vignette, this paper hopes to highlight the plight of one sibling caregiver. It also emphasises on the anomaly currently existing in the Malaysian tax rules in respect of tax relief for sibling caregivers. By further drawing on the experience of two ASEAN Economic Community (AEC) member countries, namely Singapore and Thailand, this study voices the need to synchronise tax relief conferred on sibling caregivers who are also taxpayers. Keywords: Autoethnography, ASEAN Economic Community (AEC), Sibling Caregivers, Tax Policy, Tax Relief JEL Classification: I31, I38, M48